Welcome speech of the deputy Jogorku Kenesh of the Kyrgyz Republic Turusbekov Baktybek Sagyndykovich at the III International round table "Biological and food security, ecology and modern digital technologies" (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The abstract is missing.
Keywords: There are no keywords.